Nurses’ knowledge of HIV/AIDS - Siebers, Robert (International Journal Of Community Medicine And Public Health, 2017)
A recent article in this journal presented the knowledge and attitude towards caring for HIV/AIDS patients in Nigeria. The authors, in their discussion section, state that the majority of their respondents had a good knowledge of HIV/AIDS in contrast to the results of a South African study of nurses. In support of that statement the authors cite the study of Juan et al and hypothesise that this difference may be due to the fact that their study was done in urban areas of Nigeria while the study by Juan et al was done in a rural area of South Africa.